Patterns, procedures, and indications for pediatric surgery in a Tanzanian Refugee Camp: a 20-year experience - Joseph V Sakran; Peter J Winch; Mohamed Abbas; Kent A Stevens; Daniel S Rhee; Zachary Obinna Enumah; Hilary Ngude; Sarah Rapaport; Amber Lekey (BMJ Publishing Group, 2023)
Background There are 103 million displaced people worldwide, 41% of whom are children. Data on the provision of surgery in humanitarian settings are limited. Even scarcer is literature on pediatric surgery performed in humanitarian settings, particularly protracted humanitarian settings.Methods We reviewed patterns, procedures, and indications for pediatric surgery among children in Nyarugusu Refugee Camp using a 20-year retrospective dataset.Results A total of 1221 pediatric surgical procedures were performed over the study period. Teenagers between the ages of 12 and 17 years were the most common age group undergoing surgery (n=991; 81%). A quarter of the procedures were performed on local Tanzanian children seeking care in the camp (n=301; 25%). The most common procedures performed were cesarean sections (n=858; 70%), herniorrhaphies (n=197; 16%), and exploratory laparotomies (n=55; 5%). Refugees were more likely to undergo exploratory laparotomy (n=47; 5%) than Tanzanian children (n=7; 2%; p=0.032). The most common indications for exploratory laparotomy were acute abdomen (n=24; 44%), intestinal obstruction (n=10; 18%), and peritonitis (n=9; 16%).Conclusions There is a significant volume of basic pediatric general surgery performed in the Nyarugusu Camp. Services are used by both refugees and local Tanzanians. We hope this research will inspire further advocacy and research on pediatric surgical services in humanitarian settings worldwide and illuminate the need for including pediatric refugee surgery within the growing global surgery movement.